Analyse Comparative De La Rentabilite Economique De L’exportation De L’ananas Frais Et De Son Jus Au Benin - Chabi Felix Biaou (European Scientific Journal, ESJ, 2018)
In recent years, the rapid increase in pineapple production has been accompanied by an increase in its exports and that of its juice to various sub-regions. To assess the profitability of these exchanges, surveys were conducted among producers, processors, and exporters. The Cost-Financial and Economic Benefit ratios, nominal and effective protection coefficients, and the ratio of comparative advantage were used in this study. The results show that the export of fresh pineapple to hinterland countries is, on the one hand, more profitable than that of pineapple juice because of the proliferation of sugar-sweetened beverages in the sub-region. On the other hand, it is more profitable than its export to Europe.